Interactive Learning Assistance with Projector-Based Educational Games to Increase Student Learning Motivation at Madrasah Ibtidaiyah Ngampungan - Muhtar Safaat; Fatma Ghoutsiatul Waro; Moch Solich; Ifan Fahmi; Robi’ul Afif Nurul ‘Aini (Ihsanniat: Jurnal Pengabdian Kepada Masyarakat, 2026)
Conventional learning tends to be monotonous and less interactive, resulting in low student learning motivation. Learning support activities using non-conventional methods are needed. Interactive support based on educational games with projector media is promoted to increase student learning motivation. The implementation of the activity includes planning, socialization, learning support, observation, and reflection. The target of the activity is students of Madrasah Ibtidaiyah (MI) Ngampungan. Data was collected using observation and documentation techniques during the activity. The results of the activity show that during the learning process, students are more enthusiastic and motivated. Students appear more active in asking questions, answering questions, and participating in learning activities. The implementation of projector-based educational games can create an interactive, fun, and competitive learning atmosphere. Projector-based educational games media helps students understand the material more easily. Projector media is an innovative alternative for schools with limited learning facilities. This activity is expected to be one of the interactive learning models that teachers can apply to improve the quality and motivation of students in elementary schools.